Talent Management and Talent Building in Upgrading Employee Performance - Alruwaili, Naif Fawzi (European Journal of Sustainable Development, 2018)
This study has three objectives. The first one seeks to determine the distinction between innate and acquired talent in relation to performance. The second objective identifies best practices in talent management that can be used by a company?s Human Resources Department (HRD). The third objective highlights activities of current employees that can be used to benchmark them as able to become talented. This study was conducted in Saudi Arabian companies operating in the Al Jouf and Northern Border Provinces. Therefore, the researcher recommends further research on companies operating outside these two provinces. A qualitative approach was used to collect data by conducting face to face semi-structured interviews with the heads of HR departments in companies in the Al-Jouf and Northern Border provinces area of the Kingdom of Saudi Arabia. Results show that talent management can be a strategic plan for organizations to improve their performance. Keywords: Talent Management, Human Resource Management, HR Practices, Employee Performance.